2010
DOI: 10.1007/s10488-010-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Services Expenditures among Children Placed in Out-of-Home Care

Abstract: This study examined Florida Medicaid mental health expenditures for children in out-of-home care. Child welfare and Medicaid administrative databases were analyzed using two-part models to identify characteristics associated with expenditures. Mental health expenditures were higher for older children, boys, children who were abused or lost their caregivers, or with a longer length of stay in out-of-home care. In contrast, African American children were less likely to have positive expenditures than White child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A total of 16 papers 116,504,587,588,[617][618][619][620][621][622][623][624][625][626][627][628] were excluded from the review of economic evidence and these are reported in Table 10. Six papers [619][620][621]623,626,628 were excluded because they did not involve an intervention and four papers 587,618,624,625 because the intervention in question did not meet criteria for inclusion, focusing on prevention rather than treatment.…”
Section: Excluded Economic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 papers 116,504,587,588,[617][618][619][620][621][622][623][624][625][626][627][628] were excluded from the review of economic evidence and these are reported in Table 10. Six papers [619][620][621]623,626,628 were excluded because they did not involve an intervention and four papers 587,618,624,625 because the intervention in question did not meet criteria for inclusion, focusing on prevention rather than treatment.…”
Section: Excluded Economic Studiesmentioning
confidence: 99%
“…Six papers [619][620][621]623,626,628 were excluded because they did not involve an intervention and four papers 587,618,624,625 because the intervention in question did not meet criteria for inclusion, focusing on prevention rather than treatment. Two records 622,627 did not have a specific focus on maltreatment, three records 116,504,588 did not meet criteria for a full economic evaluation and one record 617 was a conference abstract.…”
Section: Excluded Economic Studiesmentioning
confidence: 99%